Clinical case of leptospirosis in a woman against chronic alcohol intoxication - А.S. Sydorchuk; V.D. Sоrokhan; N.А. Bоhachyk; А.D. Drahanush; I.V. Fеldman; L.V. Hrubliak (Medičnì Perspektivi, 2022)
An interesting clinical case of leptospirosis infection in an elderly woman with a professional way of getting infection on the background of alcohol abuse has been described. The authors emphasized the clinical features of this bacterial zoonosis, considered aspects of differential diagnosis of leptospirosis with other common infectious diseases. It has been emphasized on the intricacies of a detailed epidemiological anamnesis taking in order to identify and evaluate biorisk factors for pathogenic leptospira contamination in a particular occupational environment. It has been pointed out the necessity of a complex laboratory-instrumental investigation in the infectious hospital, since the delay of hospitalization and adequate treatment can worsen the prognosis for a favorable outcome of the clinical case and recovery. Such specific laboratory methods for verifying leptospiras in the blood of patients as a reaction of microagglutination and lysis with a kit of leptospira and bacterioscopic examination of a smear in the dark field are of high sensitivity and specificity and therefore are widely used in clinical practice.